CRESCENT-BASED METASURFACE - Muslimin, Ikhwanul
Nanotechnology used to manipulate light is developing quite rapidly. One way to utilize light is to use photonic crystals that have a photonic band structure. 2D photonic crystals are generally composed of tall pillars above a substrate or holes in a substrate. By changing the shape of the photonic crystal unit cell from a cylinder or hole to another shape, different responses can be obtained from this photonic crystal scattering wave, one of which is the Fano resonance, which is an interference of a sharp resonance and a broad resonance. This resonance is interesting because it has an asymmetrical shape. To be able to analyze this resonance, it is necessary to solve the eigenvalue problem for the Helmholtz equation in the unit cell, which is parameterized by quasi-momentum to obtain the band structure of the photonic crystal. The eigenvalue problem of this system is solved by the finite-element method (FEM). By changing the illumination direction to the photonic crystal into a normal illumination, an analysis of the Fano profile of the scattering waves can be performed. In this thesis research, photonic crystals made of crescent structures on a substrate is examined. This structure produces a Fano profile in its reflectance spectrum, which is the result of mode interference produced by a sharp resonance of the crescent structure known as a dark mode and a broad resonance mode of the substrate known as a bright mode. By changing the distance between the center of the cylinders and the radius of the cylinders the position of the Fano profile can be shifted and parameters can be found to produce the best Fano profile.